Phonosymbolic Drive: More about Ergonomics in Language - Carlos Hernández Sacristán (Signifiances (Signifying))
Phonosymbolism can be considered a universal phenomenon of language. Although the materiality of the linguistic sign is associated with its meaning with a high degree of conventionality, a substratum of iconism persists (and is even required) in the configuration of the expressive means of any natural language. Phonosymbolism is thus far from being an anecdotal fact, as has often been suggested. In the following study I will try to answer some questions that allow us to support this ‘need’ for an iconic link between expressive means and meaning, which could be characterized in terms of a ‘phonosymbolic drive’. Beyond the specific products that reveal ‘phonosymbolism’, the paper explores the cognitive processes, ergonomically based, that would explain these products.